Comparative plastome and mitogenome analyses indicate that the marine prasinophyte green algae Pycnococcus provasolii and Pseudoscourfieldia marina (Pseudoscourfieldiophyceae class nov., Chlorophyta) represent morphotypes of the same species - Crépeault, Olivier (Journal of phycology, 2024)
© 2024 The Author(s). Journal of Phycology published by Wiley Periodicals LLC on behalf of Phycological Society of America.